Dietary pattern characterized by a balanced diet rich in high-quality protein intake is associated with mild initial clinical manifestations in tuberculosis - Li, Xiaona; Zhong, Zhaoyi; Liu, Yufeng; Gong, Guifang; Zhang, Yangting; Wang, Yukang; Liu, Chunchun; Wang, Qiuzhen (Frontiers in Nutrition, 2022)
Background: The relation between a single food or nutrient and pulmonary tuberculosis (TB) had been explored in many studies; however, the relation between dietary pattern and TB is still lacking. Objective: Our study aims to investigate the relationship between dietary pattern and the initial clinical manifestations in patients with TB. Materials and Methods: A cross-sectional study including 1661 patients with active-TB was conducted in Qingdao, China from 2011 to 2019. Dietary data were collected by a semi-quantitative food frequency questionnaire. Dietary patterns were determined by principal components factor analysis. Initial clinical manifestations were assessed using a combination of patient self-report clinical symptoms and the admission results indicated by TB score. The associations between dietary pattern and TB score in patients with TB was examined by logistics regression model. Results: The analysis identified four dietary patterns: meat-fruit-seafood pattern; dairy-egg pattern; beans and their products-whole grain pattern and refined grain-vegetable pattern. In a multiple adjusted model, higher adherence to meat-fruit-seafood pattern showed a protective effect on TB score (OR 0.53, 95 % CI 0.39, 0.84, P for trend=0.010) and the association was stronger in patients older than 45 years (OR 0.32, 95 % CI 0.16, 0.64, P for trend﹤0.001). The higher adherence to beans and their products-whole grain pattern was a protect factor for TB score (OR 0.57, 95 % CI 0.37, 0.87, P for trend=0.025), and the association was also observed in patients with concurrent TB and DM with a more significant effect (OR 0.33, 95 % CI 0.14, 0.80, P for trend=0.025). No significant association was found for dairy-egg pattern and refined grain–vegetable dietary pattern with TB score. Conclusions: Dietary patterns characterized by a balanced diet rich in high-quality protein, sufficient energy, as well as marine n-3 PUFA, phytochemicals, B vitamins and fiber are associated with mild initial clinical manifestations and the association is stronger in patients older than 45 years and those with concurrent TB and DM.